A COMPARATIVE ASSESSMENT OF SPOUSES RIGHTS IN MARRIAGE - Seyyed Mohsen Fali (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Family law is of particular importance in different legal systems in the world because the prosperity and achievements accomplished in families can directly or implicitly influence a country’s welfare, security, civilization, and other structures. For instance, if the family laws are inefficient in a country, divorce rates increase, and cohabitation and evasion of responsibilities result in cultural and economic disorders. When the position of the family is designated, the spouses’ rights and obligations become apparent as the foundation of the marriage contract because they decide to get married after considering the profits and losses. This comparative study investigated the rights and obligations of spouses in Imamiah jurisprudence, and the laws of Iran, the Netherlands, Canada, the United States, and Morocco. In a comparative study, the strengths and weaknesses are revealed and the issues can be resolved. This research adopted a fundamental-descriptive method. The findings include knowledge of how different countries adopt various measures with regard to family issues, the current judicial procedure, the advantages and disadvantages of domestic law, and introduction and identification of the two current systems in the interpretation and legislation of family law.